2020
DOI: 10.1088/1742-6596/1679/4/042100
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties UHMWPE/alumina nanofibers nanocomposite

Abstract: We study the effect of a new dielectric filler – alumina nanofibers (ANF) on the mechanical properties of ultra-high molecular weight polyethelene (UHMWPE). It was shown that the combination of powder granules and alumina nanofibers in the process of solvent evaporation helps to distribute uniformly the powder particles over the surface. The effect of the process of mechanical activation on the mechanical properties of the UHMWPE/ANF nanocomposite was studied. Increasing the concentration of the ANF additive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…AONF were obtained from ENAW-1199 aluminum using the molten aluminum oxidation technology [ 14 ]. The structure of the resulting AONF was similar to that used as a filler for other polymers [ 25 , 26 ]. The obtained nanofibers were synthesized with a highly oriented texture and had an extremely high aspect ratio of length, in the range of centimeters at nanometer diameters.…”
Section: Methodsmentioning
confidence: 89%
“…AONF were obtained from ENAW-1199 aluminum using the molten aluminum oxidation technology [ 14 ]. The structure of the resulting AONF was similar to that used as a filler for other polymers [ 25 , 26 ]. The obtained nanofibers were synthesized with a highly oriented texture and had an extremely high aspect ratio of length, in the range of centimeters at nanometer diameters.…”
Section: Methodsmentioning
confidence: 89%
“…Alumina nanofibers were obtained from ENAW-1199 aluminum using the molten aluminum oxidation technology [18], similar to those we used earlier [19,20], obtaining nanofibers having no more than 1% impurities. The silanization process was carried out with silanes manufactured by Millipore Sigma, Hamburg, Germany; these are 4aminobutyltriethoxysilane (ABES) with a purity of 98%, vinyltrimethoxysilane (VTMS) with a purity of 98%; and 3-methacryloxypropyltrimethoxysilane (MAMS) with a purity of 98%, and 3-glycidyloxypropyltrimethoxysilane (GlyMS) with a purity of 98% (Evonik, Wesseling, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…One of the interesting nanostructured components are alumina nanofibers obtained by the technology of melting aluminum oxidation [18]. Alumina nanofibers make it possible to strengthen polymer materials [19,20]. However, the problem of introducing nanomaterials into a polymer matrix by itself cannot provide an effective solution for the resulting composite materials without matching the nanomaterial and the polymer matrix's surface states.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, Al 2 O 3 possesses bio‐inertness load‐bearing ability, and exceptional corrosion resistance 133,134 . The Al 2 O 3 nano fiber in polyethylene (PE) mitigates the wear due to its high hardness and adhesion strength 135 . Abdul et al 136 reinforced nano Al 2 O 3 (13 nm) in UHMWPE and observed UHMWPE‐3 wt.% Al 2 O 3 coating to be more scratch resistant than that of 10 wt.% Al 2 O 3 ‐UHMWPE coating at tribological conditions; load of 12 N and sliding speed of 0.1 m/s owing to the instantaneous failure of coating as a consequence of agglomeration.…”
Section: Noncarbonaceous Fillers Based Uhmwpe Nanocompositesmentioning
confidence: 99%